Thermodynamic verification of constitutive equations for a nonlinear anisotropic body - Kurchakov, E. E. (Reports of the National Academy of Sciences of Ukraine, 2015)
Tensor linear constitutive equations for a nonlinear anisotropic body relating stress tensor components with strain tensor components are derived. These equations are analyzed using the first and second laws of thermodynamics. As a result, the invariants of the stress and strain tensors entering into the above equations appear related to one another. The nonlinearity and strength criteria in the strain tensor invariants are formulated. The physical interpretation of these criteria is presented.